The influence of everyday emotions on mucosal immunity: An intensive longitudinal modeling approach - Seizer, Lennart; Löchner, Johanna (Psychophysiology, 2024)
Mucosal immunity is a multifaceted system of immunological responses that provides a barrier against pathogenic invasion and can be regulated by psychosocial and neuroendocrine factors. The present study aims to elucidate the association between everyday emotional states, emotion regulation skills, and mucosal immunity by utilizing an ambulatory assessment approach. 30 healthy subjects (61% male; M = 30.18 years old) completed an emotion questionnaire (PANAS) and collected saliva samples via passive drool to determine salivary immunoglobulin-A (S-IgA) excretion rate three times a day over a period of 1 week. In a multi-level model, the influence of emotions on S-IgA, both on a within-subject and between-subject level, was estimated. We found that most of the variation in S-IgA (74%) was accounted for by within-subject changes rather than stable between-subject differences. On a within-subject level, negative emotions had a significant positive effect on S-IgA levels (b = 1.87, p =.015), while positive emotions had no effect. This effect of negative emotions was moderated by the individual emotion regulation skills, with higher regulation skills corresponding to smaller effects (b = −2.67, p =.046). Furthermore, S-IgA levels decreased over the course of a day, indicating circadian rhythmicity (b = −0.13, p =.034). These results highlight the possibilities of intensive longitudinal data to investigate the covariance between psychological and immunological states over time.
CRIS-Team Scopus Importer:2024-11-26
Keywords: ambulatory assessment; ecological momentary assessment; emotion; immunoglobulin; intensive longitudinal data; psychoneuroimmunology